Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1097/01.brs.0000245869.85276.f4
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Considerations for the Placement of C2 Laminar Screws

Abstract: The majority of specimens can safely accept placement of a laminar screw. This study establishes anatomic guidelines to allow for accurate screw selection and insertion. Preoperative planning is essential for safe screw placement via this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 24 publications
3
79
0
3
Order By: Relevance
“…Cassinelli et al [2] measured the laminar thickness (LT) in the narrowest laminar section in American populations and reported that more than 70% of the specimens they studied had a LT [5 mm. Several other scholars examining the LT in Korean, Chinese and Turkish populations [7,11,19] came to similar conclusions: most of the specimens they examined had a LT larger than the diameter of the commonly used cervical screw (3.5 mm).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cassinelli et al [2] measured the laminar thickness (LT) in the narrowest laminar section in American populations and reported that more than 70% of the specimens they studied had a LT [5 mm. Several other scholars examining the LT in Korean, Chinese and Turkish populations [7,11,19] came to similar conclusions: most of the specimens they examined had a LT larger than the diameter of the commonly used cervical screw (3.5 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Several other scholars examining the LT in Korean, Chinese and Turkish populations [7,11,19] came to similar conclusions: most of the specimens they examined had a LT larger than the diameter of the commonly used cervical screw (3.5 mm). Although the minimum laminar thickness required to allow for safe placement of a screw was not described, there is a common idea that a thickness [5 mm with a precise screw trajectory may be acceptable [2,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, Resnick et al [13] and Cassinelli et al [2] studied the anatomic suitability for C2 pedicle and laminar screw placement in the general adult population, and established guidelines for these techniques. However, the feasibility of such techniques in KFS patients with C2-3 CF has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%